Basic Motor Competencies – Mobak Relationships with Active Leisure Time, Sociodemographic and Anthropometric Indicators (Laisvalaikio tyrimai, 2018)
Research background. Research literature has shown that the earlier studies rather narrowly focused on motor skills and competencies in physical activities in primary school children age groups. In the early childhood children begin to explore the environment and develop motor skills in certain groups. One of them is known as the fundamental motor skills, which are divided into “self-movement” and “object movement”. “Self-movement” skills include body movements in space and are referred to as running, carrying, jumping, sliding and canter (Haywood, Getchell, 2015). “Objet-movement” skills consist of object manipulation and ability to control. “Object-movement” forms are throwing, catching, jumping, kicking, striking and tossing (Haywood, Getchell, 2005). These skills form the basis for future movement and physical activity (Clark, Metcalfe, 2012). One of the motor skills of the analytical methods is MOBAK (Herrmann et al., 2015) (the German translation of “Motorische Basiskompetenzen” (basic motor skills)) test battery, which is used in this study. We tried to discover the relationships between physical activity and sociodemographic as well as anthropometric indicators. The aim of the research was to discover the relationships between MOBAK and physical activity, sociodemographic as well as well as and anthropometric indicators. Results. Results showed that there were relationships between MOBAK and physical activity in “Object movement” factor (p > 0.05). There were no relationships between MOBAK and sociodemographic and anthropometric indicators (p < 0.05). Conclusions. MOBAK test battery has relationships with physical activity. MOBAK test battery has no relationships with sociodemographic and anthropometric indicators.Keywords: motor skills, physical activity, sociodemographic and anthropometric indicators.